MODEL ANALYSIS OF CUSTOMERS’ ATTITUDE AND BEHAVIOUR UPON INSTANT NOODLE PRODUCTS - Eduardsah .; Mohammad Wartaka (STIE Binaniaga, 2018)
This research aims to figure out the attitude and behavior of theconsumers upon instant noodles, and to find out a relative value of affectingattributes. Data resources of this research have been obtained from 200respondents in south of Jakarta. The research has applied statistics analysiscovering the analysis of multi attribute model of Fishbein, subjective norms andtheory of reasoned action. The result of fishbein attitude analysis is as follows; fromthe four attributes being evaluated, the most important one is taste variety of 2.57scores, then easy to cook of 2.54 scores, ‘halal’ (free from pig substance) of 2.48scores and easy to get the product of 2.46 scores. The smallest value is given to thepackaging attribute of 1.58 scores. It has explained that the respondents haveconsidered that the packaging attribute is not as important as the other attributes.Nevertheless its scoring is still within an important category. Refers to the four randseing evaluated and refers to the ehavior model anal sis, ndomie has hadpositive ( > 0 ) category, it means that the consumers’ ehavior for this product isgood or positive, so Indomie has gained the biggest value of 76.65 comparing withother brands. Obviously the consumers prefer to buy Indomie more than the otherbrands. The marketing strategy has applied the following efforts; as a product leader,it has to maintain the most important attribute given by the respondent; as acompetitive product, it has to find out the weaknesses of the leader trustworthy value.However as the follower, it has to improve the respondents’ trust for the attri utesbeing evaluated by imitating or equalizing the product leader.Keywords: fishbein, Indomie, Mie Sedap, Alhami, Gagamie, subjective norms analysis